Role of Oxidizing Agents in Leaching Process of Electronic Waste - M. Saternus; A. Fornalczyk; M. Lisińska; J. Willner (Archives of Metallurgy and Materials, 2018)
New technologies and the globalization of the electrical and electronic equipment market cause a continuous increase in the amount of electrical and electronic waste. They constitute one of the waste groups that grows the fastest in quantity. The development of the new generation of electrical and electronic devices is much faster than before. Recently attention has been concentrated on hydrometallurgical methods for the recovery of metals from electronic waste. In this article the role of an oxidizing agent, mainly ozone and hydrogen peroxide was presented in hydrometallurgical processes. Leaching process of printed circuits boards (PCBs) from used cell phones was conducted. The experiments were carried out in the presence of sulfuric acid and ozone as an oxidizing agent for various temperatures, acid concentration, ozone concentration. As a result, the concentrations of copper, zinc, iron and aluminum in the obtained solution were measured. The obtained results were compared to results obtained earlier in the presence of hydrogen peroxide as an oxidizing agent and discussed.